Pendekatan Dan Kajian Sosiologi Pendidikan Islam, Hubungan Pendidikan Islam Dengan Keluarga, Sekolah Dan Masyarakat, Serta Potret Birokrasi Pendidikan Di Indonesia - Anisa Mufidhatul Qoiriyah; Binti Maunah (Al-Riwayah : Jurnal Kependidikan, 2022)
The purpose of this study is to find out the description of the various approaches in the sociology of Islamic education, the study of the sociology of education, how the relationship between Islamic education and family, school, and society, and a portrait of the education bureaucracy in Indonesia. The method in this research is to use the library method. The result of this research is that the sociological approach is divided into 3 types, namely the individual approach, the social approach, and the interaction approach. The study of the sociology of education includes problems in social relations in education. The relationship of Islamic education with family, school, and community is a complementary relationship in educating, managing, and supporting Islamic education. The portrait of the bureaucracy in Indonesia is still blurry with the problems of quality and public services, this requires the government to carry out reforms for a better future of the education bureaucracy.